Sequential Requests and the Problem of Message Sampling - Cantrill, James Gerard ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
S. Jackson and S. Jacobs's criticism of "single message" designs in communication research served as a framework for a study that examined the differences between various sequential request paradigms. The study sought to answer the following questions: (1) What were the most naturalistic request sequences assured to replicate "foot-in-the-door" (progressively reasonable requests) and "door-in-the-face" (an outrageous request followed by more reasonable requests) effects? (2) To what extent did the subjects' perceptions of request-effort and request-novelty collide and result in different compliance probabilities? and (3) How stable were subjects' impressions of the request sequences and to what degree were the subjects in agreement concerning request characteristics? Subjects, 84 intermediate-level speech communication students, were presented with a range of requests involving a number of different target behaviors. Results showed that subjects exhibited different compliance rates and perceptions about the novelty and/or effort associated with requests. However, the extent to which subjects' responses did not follow a pattern suggestive of a systematic convergence or divergence of perceptions associated with the requests could not be entirely accounted for by either dimension alone, or by a simple adaption level explanation. The study achieved a better understanding of which request sequences would be most natural in college situations. (Tables of data and a four-page reference list are included.) (JD)
ERIC Note: Paper presented at the Annual Meeting of the Eastern Communication Association (77th, Atlantic City, NJ, April 30-May 3, 1986).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attribution Theory; Communication Research; Communication (Thought Transfer); Interpersonal Communication; Persuasive Discourse; Sequential Approach; Social Attitudes; Social Cognition; Sequential Requests; Reports, Research; Speeches/Meeting Papers